Communicating about agri-food processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
What better than a lively debate to stimulate ideas on The Role of Information and Communication in the Development of Small and Medium Agri-food Processing Units in Africa ?...